Transformasi Pembelajaran di Era AI: Studi Dampak Teknologi Kecerdasan Buatan Terhadap Mahasiswa Pendidikan Sosiologi FKIP Universitas Mataram - Firmansyah, Agung; S, Sakmawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This article focuses on that dynamic, by highlighting how AI technologies are starting to affect the quality of learning of students of Mataram University’s FKIP Sociology of Education Studies Program. Sociology education, which has hitherto relied on critical thinking, social reflection, and interpretation of societal phenomena, faces new challenges as AI-based assistive tools such as ChatGPT, Grammarly, and various learning analytics systems begin to be widely used by students. AI, in practice, is capable of providing incredible ease in helping students access the literature, understand theories, compose arguments, and even produce coherent scientific narratives. The study employed a descriptive qualitative approach with data collection techniques through in-depth interviews, classroom participatory observations, as well as content analysis of alleged AI-assisted student tasks involving AI assistance. Findings showed that there were three major tendencies among Mataram University’s FKIP Sociology Education students in responding to the presence of AI. First, AI improves learning efficiency. Students felt helped in understanding abstract concepts in sociology such as functional structural theory, symbolic interactionism, and conflict theory. AI also helps them compose essays and assignments more systematically. Most respondents stated that AI “facilitates” them absorbing and expressing academic understanding. Second, AI encourages dependency and risks decreasing critical thinking capacity. Students tend to accept information from AI without a deep reflection process. Third, issues of academic ethics arise. Multiple student assignments showed high editorial similarity, uniform argumentation structures, as well as unverified references, suggesting possible unwise use of AI. This raises concerns about academic integrity and the authenticity of study findings. The presence of AI should not be viewed negatively.